Harmonization of medical device labelling standards: Challenges and opportunities between the EU and US - LOSHIKA K; KAMARAJ R (The Bioscan, 2025)
The labelling of medical devices is a critical component in the safety products, as well as, their understanding by the user and their governmental requirements. Due to the constant integration of the global market, the manufacturer dealing with multiple markets needs to contend with the dissimilar regulatory regimes created by the key regulatory organizations, especially the United States Food and Drug Administration (USFDA) and the European Medicines Agency (EMA) working within the Medical Device Regulation (MDR 2017/745). This is a critical comparison of the labelling requirements of medical device in the US and EU with reference to law provisions, the necessary elements of a label, the required language, the Unique Device Identification (UDI) systems and the post market requirements. Convergence initiatives, regulating manufacturers who are working in two jurisdictions and future leanings to global harmonisation are also raised in the article. The study under consideration should benefit regulatory professionals, manufacturers, and policymakers in such a way that it helps them understand and approach regulatory compliance with labelling in two of the world most influential regulatory systems.